Determination of antioxidant capacity using the biological system bacteriophage P22/bacterium salmonella typhimurium - Gião, Maria S. (2010)
Bacteriophage/bacterium systems have been employed in the past in assays for virucidal activity. A novel application of one such system is proposed here for the in vivo determination of antioxidant capacity. It was shown that an antioxidant such as gallic acid can effectively protect against oxidative damage brought about by H2O2sbut only within a narrow range of concentrations (i.e., from 250 to 500 mg L-1); ascorbic acid, on the other hand, did not exhibit any protective effect against H2O2. Finally, neither ascorbic nor gallic acid demonstrated a virucidal effect. The P22/Salmonella typhimurium model system thus proved to be useful in the assessment of antioxidant capacity in vivo, at least using those two alternative model antioxidants.